2017
DOI: 10.1016/j.bica.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Spaces for Cognitive Architectures: A lingua franca for different levels of representation

Abstract: During the last decades, many Cognitive Architectures (CAs) have been realized adopting different assumptions about the organization and the representation of their knowledge level. Some of them (e.g. SOAR (Laird, 2012)) adopt a classical symbolic approach, some (e.g. LEABRA O'Reilly and Munakata (2000)) are based on a purely connectionist model, while others (e.g. CLARION (Sun, 2006)) adopt a hybrid approach combining connectionist and symbolic representational levels. Additionally, some attempts (e.g. biSOAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
(47 reference statements)
0
27
0
Order By: Relevance
“…1. Vector-symbolic architectures (Gayler 2003) and conceptual spaces (Lieto, Chella, and Frixione 2017) prove that symbolic systems, such as ACT-R (Anderson and Lebiere 1998), can arise from distributed connectionist networks. As such, the choice of symbolic, vector symbolic, or connectionist is a matter of a model's level of description, rather than a theoretical claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Vector-symbolic architectures (Gayler 2003) and conceptual spaces (Lieto, Chella, and Frixione 2017) prove that symbolic systems, such as ACT-R (Anderson and Lebiere 1998), can arise from distributed connectionist networks. As such, the choice of symbolic, vector symbolic, or connectionist is a matter of a model's level of description, rather than a theoretical claim.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, what is known as the vector-symbolic (Gayler 2003;Plate 1995) or conceptual spaces (Lieto, Chella, and Frixione 2017) approach to modelling explicitly provides an account at both symbolic and sub-symbolic levels of description. In computational, vector-based models of memory, a to-be-remembered item is represented as a vector.…”
Section: Choice Of Representation Schemementioning
confidence: 99%
“…Such a layer is suited i) to extend the knowledge stored in the Long Term Memory of the individual agents; and ii) to provide a more advanced -shared across the architectures-set of reasoning procedures to query, retrieve and reason on conceptual knowledge coupling standard and common-sense reasoning procedures. Such procedures contribute to fill the gap between the existing cognitive architectures and the cat- 13 For the reasons explaining why the framework of the Conceptual Spaces can be considered in Cognitive Architectures an efficacious, intermediate, representational level connecting symbolic and sub-symbolic representations and what are the advantages offered by such framework with respect to some of the main problems affecting the representational level of CAs we refer to [10,33]. egorization heuristics used by human cognition and not previously available (or only partially available) in those systems [38].…”
Section: Discussionmentioning
confidence: 99%
“…Most existing approaches try to induce conceptual spaces based on distributional semantics by directly accessing huge amounts of textual documents to extract the multidimensional feature vectors that de- 5 It has been shown that such framework presents some advantages if introduced, in general cognitive architectures, as intermediate representational level between the symbolyc and the subsymbolic one (for more details on this issue we remind to [33]. scribe the conceptual spaces [13].…”
Section: The Systemmentioning
confidence: 99%
“…On the other hand this aspect can be formally handled by recurring to Conceptual Spaces (as shown in [47,51]). …”
Section: Manhattan Distance Etc)mentioning
confidence: 99%